KORELASI NUTRIEN TERLARUT DENGAN STRUKTUR KOMUNITAS PLANKTON DI TAMBAK MANGROVE BLANAKAN, KAB. SUBANG - Joni Haryadi; Hadiyanto Hadiyanto (Graduate School Bogor Agricultural University (SPs IPB), 2012)
Research potential of nutrients and their effects on plankton in the pond was done in mangrove [tambak terbuka (TB), tambak tumpangsari (TS), tambak tanah timbul (TT) and tambak perhutani (TP)] Blanakan. Data collection was dissolved nutrients (ammonium, nitrite, nitrate and phosphate) and plankton performed at each station using a bottle and plankton net sampler no. 25. The results showed that the concentration of ammonium, nitrite, nitrate and ranged 0,0075 to 0,6247 ppm, nitrite ranged 0,0109 to 0,0289 ppm, nitrate ranged 0,0150 to 0,1040 ppm and phosphate ranged 0,0097 to 0,1816 ppm. Diversity index of plankton in mangrove ponds Blanakan ranged 1,51 to 2,34, the equitabilty index ranged 0,66 to 0,89 and dominance index ranged 0,16 to 0,32 . The results of the regression analysis to dissolved nutrient to plankton structure community showed that dissolved nutrients can increase the abundance of plankton (80, 09 % and 67 %.), dominance index (9, 94 % and 7, 49%) but lowered its diversity (7, 76% and 11, 67 %.) and equitability of plankton (81, 20 % and 62, 92 %).Keywords: correlation, nutrients, plankton, mangrove pond, Blanakan